A longitudinal analysis of reciprocal relationships between actual and perceived motor competencies and physical self-concept in primary-school age children. (November 2022) - Strotmeyer, Anne; Herrmann, Christian; Kehne, Miriam
Abstract: Physical self-concept (PSC) and motor competencies are important factors in view of the development of a physically active lifestyle. There are research gaps regarding longitudinal studies of these relationships. This article presents findings of a longitudinal study ( n  = 200; 58% girls, M  = 8.84 ± 0.63 years) at three primary schools. The aim of this study was to analyze the relationship between actual motor competencies (AMC) and perceived motor competencies (PMC) and PSC. Therefore, manifest path models in cross-lagged design were performed. Results show that correlations between PMC and AMC increased over time and were stronger in object control than in locomotor. Effects of AMC on PSC were more strongly mediated by PMC in object control than in locomotor. To promote physical activity, developing strategies should be aimed at the acquisition of AMC, particularly in object control, and PMC, especially in locomotor, during childhood. Highlights: Correlations between perceived and actual motor competencies were stronger in object control than in locomotor. Correlation between perceived and actual competencies increased from baseline (t1) to follow up (t2) in object control. In object control, actual motor competencies at t1 were largely related to changes in self-perception at t2. Self-perception at t1 had no effect on changes in actual motor competencies in object control at t2. In locomotor, actual motor competencies at t1 were slightly related to changes in self-perception at t2. Especially self-perception at t1 predicted changes in actual motor competencies in locomotor at t2.